2005
DOI: 10.3928/1542-8877-20050301-08
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia With Monitored Anesthesia Care for Surgical Repair of Selected Open Globe Injuries

Abstract: * BACKGROUND AND OBJECTIVE: To investigate clinical features and visual acuity outcomes associated with the use of regional anesthesia with monitored anesthesia care (RA/MAC) versus general anesthesia for open globe injuries in adult reparable eyes. * PATIENTS AND METHODS: Retrospective, consecutive case series including all adults with open globe injuries repaired at Bascom Palmer Eye Institute between 2000 and 2003. * RESULTS: The study included 238 eyes of 238 patients with a median age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Subsequently, Scott et al performed a retrospective study of 238 open globe injuries treated between 2000 and 2003 and found that patients managed with sedation and locoregional anesthesia were more likely to have anterior wounds ( P <0.001) and less likely to have an afferent pupillary defect (12% vs 43%). 14 In this study, the use of local anesthesia was not associated with the increased risk of extrusion of globe contents and did not result in impairment in long-term visual outcome. Many centers continue to manage ocular trauma under GA because providers are uncomfortable administering blocks to the traumatized eye.…”
Section: Ocular Traumamentioning
confidence: 46%
“…Subsequently, Scott et al performed a retrospective study of 238 open globe injuries treated between 2000 and 2003 and found that patients managed with sedation and locoregional anesthesia were more likely to have anterior wounds ( P <0.001) and less likely to have an afferent pupillary defect (12% vs 43%). 14 In this study, the use of local anesthesia was not associated with the increased risk of extrusion of globe contents and did not result in impairment in long-term visual outcome. Many centers continue to manage ocular trauma under GA because providers are uncomfortable administering blocks to the traumatized eye.…”
Section: Ocular Traumamentioning
confidence: 46%
“…In a later study, Scott et al reviewed a further 238 OGI and compared visual outcomes in relation to regional versus general anesthesia. 16 This study found no difference in terms of improvements in post versus pre-operative visual acuity between the two groups. Moreover, McClellan et al performed a retrospective review of 448 OGI at their institution over an eleven-year period.…”
Section: Open Globe Injurymentioning
confidence: 52%
“…6,7 Based on data in the current study, ophthalmologists and anesthesiologists may consider this type of anesthesia as a reasonable alternative to general anesthesia for the repair of open globe injuries in selected patients.…”
Section: Discussionmentioning
confidence: 93%